Antimutagenicity of a suberin extract from Quercus suber cork. - Krizková, L; Lopes, M H; Polónyi, J; Belicová, a; Dobias, J; Ebringer, L (Mutation research, 1999)
The possible protective effect of a suberin extract from Quercus suber cork on acridine orange (AO)-, ofloxacin- and UV radiation-induced mutagenicity (bleaching activity) in Euglena gracilis was examined. To our knowledge, the present results are the first attempt to analyse suberin in relation to mutagenicity of some chemicals. Suberin exhibits a significant dose-dependent protective effect against AO-induced mutagenicity and the concentration of 500 micrograms/ml completely eliminates the Euglena-bleaching activity of AO. The mutagenicity of ofloxacin is also significantly reduced in the presence of suberin (125, 250 and 500 micrograms/ml). However, the moderate protective effect of suberin on UV radiation-induced mutagenicity was observed only at concentrations 500 and 1000 micrograms/ml. Our data shows that suberin extract from Q. suber cork possess antimutagenic properties and can be included in the group of natural antimutagens acting in a desmutagenic manner.
Keywords: Acridine Orange; Acridine Orange: toxicity; Animals; Antimutagenic Agents; Antimutagenic Agents: pharmacology; Euglena gracilis; Euglena gracilis: drug effects; Euglena gracilis: genetics; Euglena gracilis: radiation effects; Lipids; Membrane Lipids; Membrane Lipids: pharmacology; Mutagenicity Tests; Mutagenicity Tests: methods; Mutagens; Mutagens: toxicity; Ofloxacin; Ofloxacin: toxicity; Plant Extracts; Plant Extracts: pharmacology; Plant Shoots; Plant Shoots: chemistry; Spectrophotometry, Ultraviolet; Superoxides; Superoxides: metabolism; Trees; Trees: chemistry; Ultraviolet Rays